2001
DOI: 10.1029/2000jd900722
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and modeling of quasi‐monochromatic atmospheric gravity waves observed over Urbana Illinois

Abstract: Abstract. From analyzing nine months of airglow imaging observations of atmospheric gravity waves (AGWs) over Adelaide, Australia (35øS) [Walterscheid et al., 1999] have proposed that many of the quasi-monochromatic waves seen in the images were primarily thermally ducted. Here are presented 15 months of observations, from February 1996 to May 1997, for AGW frequency and propagation direction from a northern latitude site, Urbana Illinois (40øN). As Adelaide, Urbana is geographically distant from large orograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
167
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(180 citation statements)
references
References 35 publications
12
167
0
1
Order By: Relevance
“…Accordingly, we also use the horizontal wind model (HWM) [Hedin et al, 1996] to define the mean winds throughout the atmosphere for May 8/9. Tidal variations are quite strong in the lower thermosphere, and therefore the mean winds and the associated wave reflection may depend quite sensitively on local time [Hecht et al, 2001]. Therefore for the HWM winds we selected three different local times (0000, 0200, and 0400 LT), which corresponds to the time period analyzed in detail by W2000.…”
Section: Model Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we also use the horizontal wind model (HWM) [Hedin et al, 1996] to define the mean winds throughout the atmosphere for May 8/9. Tidal variations are quite strong in the lower thermosphere, and therefore the mean winds and the associated wave reflection may depend quite sensitively on local time [Hecht et al, 2001]. Therefore for the HWM winds we selected three different local times (0000, 0200, and 0400 LT), which corresponds to the time period analyzed in detail by W2000.…”
Section: Model Inputmentioning
confidence: 99%
“…The full-wave model allows us to assess the strength of reflection while also providing values of 4)(•) for several airglow emissions. The model has been used extensively to simulate the ducting of very short period gravity waves in the lower thermospheric thermal duct while also including mean wind effects [Hecht et al, 2001 ]. Using this model, these studies have been able to explain the observed seasonal variation of the preferred azimuths of gravity wave propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al, 1999;Walterscheid et al, 1999;Hecht et al, 2001), some with strong meridional anisotropy. Walterscheid et al (1999) suggested this could be due to wave ducting rather than wind filtering effects.…”
Section: Gravity Wave Anisotropymentioning
confidence: 99%
“…We have not performed simulations using either measured winds or using winds based on either numerical or empirical models. Climatological wind profiles have been used previously in wave-ducting simulations using our full-wave model by Hecht et al [2001 ]. These wind profiles combined empirical winds [Hedin et al, 1996] with a wind climatology for Urbana, Illinois, based on University of Illinois MF radar measurements (a good discussion of the MF radar winds is given by Franke and Thorsen [1993]).…”
Section: Isothermal Nonadiabatic Ductingmentioning
confidence: 99%
“…wave may be internal in the region of local minimum of r B , and become evanescent at some distance either side of this where r• has increased [Hines, 1960;Wickersham, 1968;Hecht et al, 2001 ]. In this case, the wave would be thermally ducted.…”
mentioning
confidence: 99%